2013
DOI: 10.5489/cuaj.181
|View full text |Cite
|
Sign up to set email alerts
|

Improved Wait Time Intervals for Prostate Cancer Patients in a Multi-Disciplinary Rapid Diagnostic Unit Compared to a Community-Based Referral Pattern

Abstract: Background: Wait times in cancer diagnosis and treatment may significantly affect a patient's treatment outcome, prognosis and quality of life. The purpose of this study was to capture wait time intervals for patients with prostate cancer treated with radiotherapy (RT) at the Odette Cancer Centre, Toronto, Ontario, Canada and to compare patients diagnosed in a rapid diagnostic unit (RDU) versus the usual community referral process. Methods: Patients agreed to participate in the study during their RT planning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Details about the characteristics of each diagnostic centre can be found in the Supplementary File . Sixteen quasi-experimental studies [ 14 , 15 , 17 23 , 25 28 , 30 , 31 , 33 ], three economic evaluations [ 29 , 32 , 37 ] and one randomised controlled trial (RCT) [ 38 ] were included. The studies were conducted in Spain ( n = 11), UK ( n = 5), and Canada ( n = 4), and were published between 1998 and 2021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details about the characteristics of each diagnostic centre can be found in the Supplementary File . Sixteen quasi-experimental studies [ 14 , 15 , 17 23 , 25 28 , 30 , 31 , 33 ], three economic evaluations [ 29 , 32 , 37 ] and one randomised controlled trial (RCT) [ 38 ] were included. The studies were conducted in Spain ( n = 11), UK ( n = 5), and Canada ( n = 4), and were published between 1998 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies described diagnostic centres located within hospital settings ( n = 19) with only one study describing a diagnostic service located within the community setting [ 15 ]. Ten studies were specific to cancer diagnoses [ 14 , 19 21 , 25 , 27 , 30 , 31 , 37 , 38 ], six reported on the diagnosis of several health conditions [ 18 , 22 , 23 , 29 , 32 , 33 ] and three studies covered a single health condition including severe anaemia ( n = 1) [ 28 ], fever of uncertain nature (FUN) ( n = 1) [ 17 ], and multiple sclerosis (MS) ( n = 1) [ 26 ]. One study did not report a health condition of interest [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The goal act of DAP is to improve timely access to care for prostate cancer patients. Early evidence showed that the DAP reduced wait times from cancer suspicion to radiotherapy by on average 2 months compared to standard community practice (7). In the efforts to reduce waiting time, multiparametric magnetic resonant imaging (mpMRI) is strongly recommended in men candidate for prostate biopsy or in men enrolled in active surveillance protocols (8).…”
Section: Original Papermentioning
confidence: 99%
“…Our group has already shown that wait times from suspicion to radiation treatment is, on average, two months shorter in the GGWPC vs. standard community practice (183 vs. 138 days, p=0.046). 6 Patients are referred from general practitioners or community urologists if they have an elevated prostate-specific antigen (PSA) in the absence of instrumentation, abnormal digital rectal examination (DRE) or abnormal imaging suggestive of PCa. Patients are seen by one of five urologists and their prostate cancer risk assessed within two weeks of referral.…”
Section: Introductionmentioning
confidence: 99%